Rethinking corticosteroids use in oncology - Martinez, Pierrick; Sabatier, Jean-Marc (Frontiers in Pharmacology, 2025)
Corticosteroids (CSs), widely used in oncology for their anti-inflammatory and immunosuppressive properties, help manage cancer-related symptoms and side effects. However, their long-term use may negatively affect patient survival and exacerbate tumor progression. Elevated glucose and glutamine metabolism, disruption of vitamin D levels, and alterations in the microbiome are some of the key factors contributing to these adverse outcomes. Approaches such as ketogenic diets, fasting, sartans, and vitamin D supplementation have shown promise in providing similar benefits to CSs while mitigating the risks associated with the mechanisms identified as contributing to tumor progression. This perspective underscores the necessity for a reevaluation of CSs use in cancer care and advocates for further research into safer, more effective therapeutic strategies.